The effect of computer-assisted instruction, interest and gender on pupils’ achievement in basic science in primary schools in Ibadan Oyo state, Nigeria (2012)
The use of instructional materials may not be limited to a particular field of study. Effective teaching and learning of basic science at primary school level could depend to a large extent on adequate use of instructional materials. This is because children at this age level tend to learn better when taught with real objects that they can see and touch. However, available evidence indicates that, despite previous efforts and methods used in teaching, performance in basic science is still very low. This study investigated the effect of computer assisted instruction (CAI), gender and aiding pupils develop positive interest as they predict primary five pupil's achievement in basic science. Pretest-posttest, control group quasi-experimental design involving a 2 x 2 x 2 factorial matrix was adopted. Purposive sampling technique was used to select 40 primary five (5) pupils' in two private schools in Ibadan, Oyo state. Two Valid and reliable instruments basic science test (p= 0.83) and interest in basic science (P=0 .724) were used for data collection. Data were analysed using analysis for covariance (ANCOVA) at 0.05 level of significance. While Sidak post hoc test was used to explain the direction of significance between the groups. Pupils who were exposed to treatment performed significantly better in basic science test (F(1,39) =11.015 ; p< 0.5) as well as exhibited positive interest (F(i,39) - 15.898, p < 0.5) than those who were not. There is a significant interaction effect of treatment, interest and gender on pupils performance in basic science (F(i, 39) = 11.899; p< 0.5). Further, majority of the boys who participated exhibited positive interest (x= 22.726) towards basic science when computer was used as instructional material than the girls (x= 18.820). The implications of the findings were discussed with a view to improving teaching-learning activities and improving dispositions of learners at school